Pengaruh Quality Of Work Life Motivasi Dan Kepuasan Kerja Terhadap Komitmen Organisasional Pada Guru Dan Karyawan Yayasan Insan Mulia Malang - Annisa Mutmainah; Pardiman Pardiman; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of quality of work life, motivation, and job satisfaction to commitment in Teachers and Employees of Insan Mulia Foundation Malang. The data used in this study uses primary data and secondary data. The study population was teachers and employees of Insan Mulia Foundation Malang, while the sample in this study were 51 respondents. The analytical method used in this study is Instrument Test, Normality Test, Classic Assumption Test, Multiple Linear Regression, Hypothesis Test, and Coefficient Determination Test. From the results of the study showed that the quality of work life and motivation did not have a significant negative effect on commitment. Another case with , job satisfaction variables that have a positive effect and significant on commitment. Simultaneously quality of work life, motivation, and job satisfaction have a significant effect on commitment in Teachers and Employees of Insan Mulia Foundation Malang. Keywords: Quality of Work Life, Motivation, Job Satisfaction, and Commitment